(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
This research is motivated by the efforts of the Darul ’Ulum Islamic Boarding School Muaro Jambi students in overcoming the symptoms of Fear of Missing out Excessive use of Social Media. The research objective was to determine the role of interpersonal communication in overcoming the symptoms of Fear of Missing Out (FoMO) for students who use social media. The method used in this research is qualitative. Interviews were conducted with 21 informants selected by purposive sampling. Data analysis uses the Miles and Huberman method. The results of the study show that the impact of fear of missing out for students is experiencing anxiety if they do not access social media, social media becomes a medium of expression, experiencing toxic productivity and the emergence of apathy. The causes of the symptoms of fear of missing out are the desire to always be connected with other people, the intensity of excessive use of social media and always accessing social media even without interest. Interpersonal communication efforts in overcoming thesymptoms of fear of missing out students, namely, limiting the use of social media, adopting the Joy of missing out (Jomo) approach, increasing openness among fellow students, increasing empathy and providing mutual support.